2019
DOI: 10.1016/j.compstruct.2019.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Isogeometric analysis for size-dependent nonlinear thermal stability of porous FG microplates

Abstract: In this article, we present for the first time a research analysis for the size-dependent effects on thermal buckling and post-buckling behaviors of functionally graded material micro-plates with porosities (imperfect FGM) using isogeometric analysis. A seventh-order shear deformation plate theory associated with the modified couple stress theory (MCST) is particularly imposed to capture the size-dependent phenomenon within imperfect FGM micro-plates. The material properties of imperfect FGM micro-plates with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(36 citation statements)
references
References 64 publications
0
35
0
1
Order By: Relevance
“…1. As a consequence, the associated Young's modulus E, shear modulus G, Poisson's ratio ν, and thermal expansion coefficient α can be extracted based on the modified rule of mixture in the following forms [17]:…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…1. As a consequence, the associated Young's modulus E, shear modulus G, Poisson's ratio ν, and thermal expansion coefficient α can be extracted based on the modified rule of mixture in the following forms [17]:…”
Section: Materials Propertiesmentioning
confidence: 99%
“…There are many reasons which motivate a large number of scientists across the world to conduct theoretical and experimental research to shed light on the influence of porosities on various engineering structures made of FGMs. One of the most significant motivations is to reduce the impact of porosities on the material strength [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Thanh et al [17] presented a novel research to investigate the size-dependent effects on the thermal stability of FGM micro-plates with three types of porosity dispersion patterns, including even, uneven, and logarithmic uneven.…”
Section: Introductionmentioning
confidence: 99%
“…Le Thanh et al 8 developed a thermomechanical size-dependent model using finite element method for predicting the stress, thermal defection, and critical buckling load of composite microplates laminates based on the Reddy plate theory together with new modification of couple stress theory. For the first time, Le Thanh et al 9 used isogeometric analysis for the size-dependent impacts on the post-buckling and thermal buckling behaviors of functionally graded micro-plates with porosities.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the respond of plate based on Reissner-Mindlin was investigated with mesh free reinforced by the moving Kriging interpolation [38,39]. Moreover, the isogeometric analysis was implemented to explain the nonlinear thermal stability of functionally graded porous micro-plate [40]. It was concluded that, porous micro-plate gives higher critical buckling and postbuckling temperature compared with perfect FGM micro-plate.…”
Section: Introductionmentioning
confidence: 99%